Analysis of a nonlinear discrete dynamical system, signal coding and reconstruction - Tlemçani, Mouhaydine (2012)
In this paper, we present a study of different iterated maps in which we are looking for invariants that link their dynamics. Various approaches of conductivity of dynamical systems are analyzed looking for real physical ex- amples. The notion of conductance of a discrete nonlinear dynamical system is linked to a physical time dependent example. The time series issued from a physical system behavior are processed from a new point of view in order to extract hidden information.